The elephant in the room: Exploring the influence and participation of patients in infection‐related care across surgical pathways in South Africa and India. (31st January 2023) - Nampoothiri, Vrinda; Mbamalu, Oluchi; Surendran, Surya; Bonaconsa, Candice; Pennel, Timothy; Boutall, Adam; Gopal, Kirun; Castro Sanchez, Enrique; Dhar, Puneet; Holmes, Alison; Singh, Sanjeev; Mendelson, Marc; et al.
Abstract: Objective: The irrational use of antibiotics is a leading contributor to antibiotic resistance. Antibiotic stewardship (AS) interventions predominantly focus on prescribers. This study investigated the influence and participation of inpatients in infection‐related care, including antibiotic decision‐making, within and across two tertiary hospitals in South Africa (Cape Town) and India (Kerala). Methods: Through ethnographic enquiry of clinical practice in surgical pathways, including direct nonparticipant observation of clinical practices, healthcare worker (HCW), patient and carer interactions in surgical ward rounds and face‐to‐face interviews with participants (HCWs and patients), we sought to capture the implicit and explicit influence that patients and carers have in infection‐related care. Field notes and interview transcripts were thematically coded, aided by NVivo 12® Pro software. Results: Whilst observational data revealed the nuanced roles that patients/carers play in antibiotic decision‐making, HCWs did not recognize these roles. Patients and carers, though invested in patient care, are not routinely involved, nor are they aware of the opportunities for engagement in infection‐related decision‐making. Patients associated clinical improvement with antibiotic use and did not consider hospitalization to be associated with infection acquisition or transmission, highlighting a lack of understanding of the threat of infection and antibiotic resistance. Patients' economic and cultural positionalities may influence their infection‐related behaviours. In the study site in India, cultural norms mean that carers play widespread but unrecognized roles in inpatient care, participating in infection prevention activities. Conclusion: For patients to have a valuable role in AS and make informed decisions regarding their infection‐related care, a mutual understanding of their role in this process among HCWs and patients is crucial. The observed differences between the two study sites indicate the critical need for understanding and addressing the contextual drivers that impact effective patient‐centred healthcare delivery. Patient or Public Contribution: Ethnographic observations and interviews conducted in this study involved patients as participants. Patients were recruited for interviews after obtaining signed informed consent forms. Patients' identities were completely anonymized when presenting the study findings.